2008
DOI: 10.1371/journal.pone.0001485
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Amino Acid Variation in the P2 Domain of the GII-4 Norovirus VP1 Protein Reveals Putative Variant-Specific Epitopes

Abstract: BackgroundHuman noroviruses are a highly diverse group of viruses classified into three of the five currently recognised Norovirus genogroups, and contain numerous genotypes or genetic clusters. Noroviruses are the major aetiological agent of endemic gastroenteritis in all age groups, as well as the cause of periodic epidemic gastroenteritis. The noroviruses most commonly associated with outbreaks of gastroenteritis are genogroup II genotype 4 (GII-4) strains. The relationship between genotypes of noroviruses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
135
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(145 citation statements)
references
References 26 publications
9
135
0
Order By: Relevance
“…We showed that several mutant capsids engineered in this study reacted with the conformational MAbs and therefore acquired the correct folding. However, two of the MAbs (A6 and A10) in our study lost their reactivity when residues Ala 294 and Asp 295 were mutated to Gly and Ile, respectively, confirming that residues 294 and 295 are involved in the formation of an important antigenic site (1,2,11). Thus, these data are consistent with the involvement of this epitope in diversification of GII.4 strains and in immune responses against norovirus infection.…”
Section: Discussionsupporting
confidence: 87%
“…We showed that several mutant capsids engineered in this study reacted with the conformational MAbs and therefore acquired the correct folding. However, two of the MAbs (A6 and A10) in our study lost their reactivity when residues Ala 294 and Asp 295 were mutated to Gly and Ile, respectively, confirming that residues 294 and 295 are involved in the formation of an important antigenic site (1,2,11). Thus, these data are consistent with the involvement of this epitope in diversification of GII.4 strains and in immune responses against norovirus infection.…”
Section: Discussionsupporting
confidence: 87%
“…Allan et al (1) recently compared the reactivities of five MAbs against a pre-and post-2002 epidemic GII.4 strain and identified a conformational epitope(s) composed of residues 294 to 296 and 393 to 395. Interestingly, both of these regions were previously predicted to be epitopes using bioinformatic methods (1,16,28) and were later verified by molecular analyses (1,29). The carbohydrate blockade potential of these antibodies was never tested, so the role of this site in escape from herd immunity is uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…P2 represents the most exposed polypeptide on the surface of the viral particle and determines its interactions with potential neutralizing antibodies and with histo-blood group antigens (HBGAs) (10,12,28,29,32). The P2 domain of the major capsid protein of GII.4 strains is evolving rapidly, resulting in new epidemic strains with altered ligand binding properties and antigenicity (1,5,7,15,29,41,43).…”
mentioning
confidence: 99%
“…To date, chronic NoV infections have been identified in a range of settings where the immune status of an individual was compromised, such as transplant recipients, HIV-positive individuals, and patients with leukemia (6,13,54,68). In addition, all previous studies of NoV evolution have used only traditional sequencing methods, such as Sanger sequencing (1,14,58,66,71). No study has looked in depth at the intrahost evolution of an acute or chronic NoV infection at high resolution using next-generation sequencing (NGS) methods.…”
mentioning
confidence: 99%